2016
DOI: 10.4329/wjr.v8.i4.403
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of computed tomography findings between bacteremic and non-bacteremic acute pyelonephritis due toEscherichia coli

Abstract: On CT, urothelial thickening, diffuse peritoneal thickening, cystitis, and pulmonary congestion are more frequently observed in patients with bacteremic APN due to E. coli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In the context of APN, CT has been considered the method of choice for assessment of the extent of inflammatory involvement of renal parenchyma, detection of bilateral infections and complications, and for providing an alternative diagnosis, if applicable (1,7,8). A multiphase CT protocol (pre- and post-contrast) has been the widespread current practice (1,7,9,10,16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of APN, CT has been considered the method of choice for assessment of the extent of inflammatory involvement of renal parenchyma, detection of bilateral infections and complications, and for providing an alternative diagnosis, if applicable (1,7,8). A multiphase CT protocol (pre- and post-contrast) has been the widespread current practice (1,7,9,10,16).…”
Section: Discussionmentioning
confidence: 99%
“…elderly, immunocompromised) with atypical symptoms or no response to antibiotic therapy within 72 h (8,9). The most widely accepted CT protocol for diagnosis of APN includes at least a pre- and post-contrast scan (9), with the use of triphasic scans (pre-contrast, nephrographic, and excretory phases) still being often reported in the literature (1,10,11).…”
Section: Introductionmentioning
confidence: 99%
“…BSIs and non-BSIs. In addition, studies have been conducted comparing bacteremic and non-bacteremic pneumonia caused by S. pneumoniae and Acinetobacter baumannii ( 20 , 21 ), as well as bacteremic and non-bacteremic acute pyelonephritis due to Escherichia coli ( 22 ). Given the rapid progression and high motility of CRKP, it is still crucial to identify the risk factors for CRKP BSIs in patients in infected patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, initial CT scanning provides important information on the range of inflammation and other accompanying complications to help to establish a precise diagnosis. The use of a multiphase CT protocol (pre-and post-contrast) has been widespread in current practice in APN [2][3][4][5]. Recently, Taniguchi et al suggested that unenhanced Patients with Acute Pyelonephritis without Obstructive Uropathy and excretory CT phases are not really necessary because CT assessment of APN and urolithiasis can be accurately performed using only the late nephrographic phase [6].…”
Section: Introductionmentioning
confidence: 99%